South German Inspirations in the Armour of Late Medieval Combatants from the Silesian-Lusatian-Brandenburg-Polish Borderland. Iconographic Examples - Arkadiusz Michalak (Fasciculi Archaeologiae Historicae, 2017)
There are visible tendencies in the late medieval iconography from the Silesian-Lusatian-Brandenburg-Polish borderland, indicating strong South German inspiration in depicted armour. The presence of this kind of protection on works of art from this region can most likely be connected with political, family and artistic reasons.